Routine histopathological examination after female‐to‐male gender‐confirming mastectomy. Issue 7 (5th April 2018) - Van Renterghem, S. M. J.; Van Dorpe, J.; Monstrey, S. J.; Defreyne, J.; Claes, K. E. Y.; Praet, M.; Verbeke, S. L. J.; T'Sjoen, G. G. R.; Van Bockstal, M. R.
Abstract : Background: The number of transmen seeking gender‐confirming surgery has risen steadily throughout the last decade. Pathologists are increasingly confronted with transmale mastectomy specimens. It is not clear whether routine histopathological examination is useful. This study explored the possible benefit of routine investigation through detailed description of lesions encountered in mastectomy specimens after female‐to‐male gender‐confirming surgery. Methods: Breast tissue from a cohort of transmen was reviewed. The presence of benign and malignant breast lesions was recorded. The number of terminal duct–lobule units (TDLUs) per ten low‐power fields (LPFs) was quantified. Information on hormone therapy and morphometry was retrieved for selected patients. Results: The cohort included 344 subjects with a mean age of 25·8 (range 16–61) years at the time of surgery; the age at surgery decreased significantly over time. Older individuals presented with a significantly higher number of breast lesions. The number of TDLUs per LPF was lower in heavier breasts, but did not correlate with age. Breast lesions, either benign or malignant, were present in 166 individuals (48·3 per cent). Invasive breast cancer was found in two (0·6 per cent); one tumour was an unexpected finding. The number of breast lesions encountered on histopathological examination increased significantly when more tissue blocks were taken. Conclusion: The discovery of an unexpected breast cancer in a 31‐year‐old transman emphasizes the importance of thorough routine histopathological examination of mastectomy specimens. The number of tissue blocks taken should be based on age and breast weight. Abstract : The case for